A study of intercultural adaptation in the Sino-American joint training dual degree programs - Yueyue, Cai; Nordin, Nor Akmar; Panatik, Siti Aisyah (Frontiers in Education, 2022)
This study focuses on the factors influencing the intercultural adaptation stress and strategies of students in the Sino-American Joint Training Dual Degree Program. A total number of 400 questionnaires were distributed to Chinese students who participating in the Program and the 355 responded. Motivation and Expectation Scale, Acculturative Stress Scale for International Students and The Intercultural Adaptation Strategies Scale were adopted to measure variables. Regression test, one-way ANOVA and Structural Equation Model(SEM) were applied to analyze the survey data. The results revealed that the number of local friends, the length of stay in the US, the motivation to study abroad, and the expectation to study abroad have a negative influence on the intercultural adaptation stress of the students. The greater the number of local friends, the longer the length of stay of study abroad, the stronger the motivation and expectation to study abroad, their intercultural adaptation strategies favor integration and assimilation. Based on the findings, this study examines which teaching and learning management methods Chinese institutions should apply to help students reduce the negative effects of intercultural adaptation stress and to choose intercultural adaptation strategies for integration and assimilation when undertaking teaching and learning activities for the Sino-American Joint Training Dual Degree Program.